EVOLUTIONARY PRINCIPLES IN HUMAN CANCER IMMUNOLOGY - Luddy, Kimberly (School of Biochemistry and Immunology, 2022)
The immune system plays a fundamental role in driving the evolution of malignant cells. The anti-tumour immune response removes immunogenic tumour cells and preserves immune evasive cells. A clinically detectable tumour arises from a single transformed cell. Through millions of cell divisions, tumour cell populations diversify and acquire mechanisms to avoid destruction by the immune system. Examining the evolutionary outcomes of populations undergoing natural selection can reveal novel adaptive strategies. Evolutionary principles are used to gain insights into different aspects of cancer biology. However, these approaches have not been widely applied to cancer immunology. Here, we hypothesize that evolutionary principles can be successfully integrated into cancer immunology research to reveal novel findings with clinical potential. To explore this hypothesis, we used three approaches taken from evolutionary biology: 1) conservation of essential genes during evolution. We performed a gene conservation study on lung tumour tissue to determine essential genes at the interface of tumour and immune cell interactions. Mutations in malignant epithelial cells undergo selection. Deleterious mutations in genes that are essential for survival and proliferation undergo negative selection. Here, we apply this principle to determine the conservation levels of genes expressed in malignant epithelial cells with immune functions. We found several genes involved in antigen presentation conserved in lung cancer, in particular ERAP1/2, which has been identified as a therapeutic target by other approaches. We also found a group of natural killer cell ligands, particularly MICA, PVR, and PVRL2, conserved in wild-type and mutant KRAS tumours. Disruption of antigen presentation on epithelial cells and overexpression of inhibitory molecules are common mechanisms of malignant cell immune evasion. Our gene conservation study demonstrates that probing the outcomes of natural selection can reveal novel immune targets. 2) evolutionary costs of treatment resistance. Building on the above model and focusing on the NK ligands identified above, we next examined the evolutionary outcome of radiation resistance. Adaptive strategies that arise under strong selection pressures often have an associated fitness cost. By evaluating an isogenic cell line model of prostate cancer, we found that radiotherapy resistance increases expression of natural killer cell ligands, MICA/B, PVR, and PVRL2, on tumour cells resulting in increased sensitivity to NK cell-mediated killing. Our pre-clinical study revealed selective targeting of radiation-resistant cells by NK cells. 3) evolutionary double bind. A ‘double bind’ exists when resistance to one treatment increases the sensitivity to a second treatment. Selective targeting of radiation-resistant populations by NK cells is a double bind. Using our isogenic radiation-sensitive and resistant prostate cancer cell lines and novel competition culture models, we show that treatment with NK cells restores the radiation-sensitive cancer cell population. We also found that radiotherapy followed by NK cell therapy reduced the number of tumour cells and controlled the outgrowth of radiotherapy resistance. This effect was amplified in samples with initially high levels of radiation resistance. We have shown that evolutionary principles applied to cancer immunology research can reveal novel targets with clinical potential. After the target is identified, we demonstrate that evolutionary principles can be used to optimize therapy schedules to exploit treatment-induced evolutionary double binds. We propose that patients will benefit from the integration of evolutionary medicine and cancer immunology to both reduce tumour burden and delay or prevent treatment resistance. We are the first to use gene conservation levels of immune-related genes for novel target discovery in clinical samples and to apply those findings to a pre-clinical model of a treatment-induced immunological double bind.
Keywords: Cancer, immunology, evolution, immune evasion, cancer ecology